The white coat public art project: using the white coat as a canvas for reflection for women in medicine. (May 2021) - Darivemula, S.; Stella, A.; Fahs, F.; Poirier-Brode, K.; Ko, K.
Abstract: Objectives: Burnout and low job satisfaction have disproportionately impacted female physicians compared with their male counterparts, with gender-specific oppression and bias in the workforce. This project aims to address the relationship of women in medicine to their chosen field through public art. Study design: A call for using the white coat as a canvas to describe positive attributes and self-reflection was shared with all American Medical Women's Association (AMWA) branches at medical schools. Methods: Students in AMWA branches created white coats, designing them to answer the posed question. Results: White coats were sent to the national conference for display, revealing certain themes, challenges, resilience, and humanization of the training and working experience for women in medicine. Conclusion: This white coat public art project directly and indirectly addresses causes of burnout and serves as a way to create community, address isolation, and empower women in medicine.